Assume that all the given functions are differentiable. 46. If u = f ( x , y ), where x = e s cos t and y = e s sin t , show that ( ∂ u ∂ x ) 2 + ( ∂ u ∂ y ) 2 = e − 2 s [ ( ∂ u ∂ s ) 2 + ( ∂ u ∂ t ) 2 ]
Assume that all the given functions are differentiable. 46. If u = f ( x , y ), where x = e s cos t and y = e s sin t , show that ( ∂ u ∂ x ) 2 + ( ∂ u ∂ y ) 2 = e − 2 s [ ( ∂ u ∂ s ) 2 + ( ∂ u ∂ t ) 2 ]
Solution Summary: The author explains that the partial derivative, partial s is computed as follows.
Find an equation of the line tangent to the graph of f(x) = (5x-9)(x+4) at (2,6).
Find the point on the graph of the given function at which the slope of the tangent line is the given slope.
2
f(x)=8x²+4x-7; slope of the tangent line = -3
Use the product rule to find the derivative of the following.
p(y) (y¹ + y²) (6y¯³-10y¯4)
Chapter 14 Solutions
Bundle: Calculus: Early Transcendentals, Loose-Leaf Version, 8th + WebAssign Printed Access Card for Stewart's Calculus: Early Transcendentals, 8th Edition, Multi-Term
Need a deep-dive on the concept behind this application? Look no further. Learn more about this topic, calculus and related others by exploring similar questions and additional content below.